Daughters, Savings and Household Finances - Xin Wen; Zhiming Cheng; Massimiliano Tani (Global Labor Organization (GLO), 2024)
We explore the link between child gender and household financial decisions within a cultural environment that strongly favours having a son. Using data from the China Household Finance Survey (CHFS), we find that the presence of a daughter is associated with a lower saving rate, consistent with the hypothesis that the relative under-supply of unmarried women generates a less competitive marriage market for families with daughters vs. those with sons. As a result, such families have lower incentives to endow their daughters with bigger asset pools to enhance their marital prospects. The correlation becomes more pronounced as the daughter approaches marriageable age, and it is more common among families where the head has low financial literacy and limited education and lives in rural areas.
Keywords: D14; G11; G51; J12; 330; daughter; household investment decisions; family savings; marriage market